Measuring TPACK and HOTS of Teacher Professional Education Students Based on Lesson Plans - Nur Wakhidah; Juhaeni Juhaeni; Safaruddin Safaruddin; Erman Erman; Shaouna Shoaib Lodhi (Journal of Innovation in Educational and Cultural Research, 2025)
The manifestation of the technological age is that humans use technology, so education must prepare professional teachers who understand technology. Technology, content, and pedagogic-based learning occurred during COVID-19, known as technological pedagogical content knowledge (TPACK). TPACK research, so far as expertise using questionnaires, rarely studied TPACK designed by teachers. This quantitative study aims to determine the ability of TPACK in lesson plans (LP) of teacher professional education (TPE) students at UIN Sunan Ampel and its effect on HOTS. Data was collected by scoring LP based on TPACK and HOTS instruments. Data on students' ability to design lesson plans were analyzed using SEM path analysis with AMOS application to measure the influence of the TPACK component (TK, CK, PK, TPK, TCK, PCK) for TPACK and HOTS. The results showed that TPACK components ((pedagogic ability (PK) and technology-based pedagogic ability (TPK)) indirectly affect TPACK. Technology-based content capability (CTK) and TPK directly affect TPACK. The TPACK component involves HOTS in a negative direction except for content capability (CT), which affects HOTS positively.